Dependency and Underdevelopment Under Globalization. Neoliberal and Neo-Developmentalist Experiences in Argentina - Wainer, Andrés (Sociedad y Economía, 2019)
Transformations suffered by global economy due to globalization have forced us to rethink the relation between dependence and underdevelopment. In this sense, the purpose of this article is to analyze if during the last two political experiences in Argentina (the “neo-development” and the return of neoliberalism) were there any substantial changes in the dependent character of their economy and in what sense they operated. For this purpose, some key variables of the evolution of the Argentine economy in recent decades are presented. Similarly, conceptual issues such as the destination of the capital gains and the role played by central instruments in a free-trade framework, like the exchange rate, are addressed. It is concluded that although neoliberal policies have deepened the dependency situation, the “neo-developmentalist” governments have not managed to promote a sustained development process either